Queers read this - Anonyme (1990)
A leaflet distributed at pride march in NY. Published anonymously by Queers.
Keywords: LGBTQIA2+; VIH; amérique du nord; amériques; approches et analyses; hétérosexisme; identités LGBTQIA2+; militance; privilèges; queer; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; violences; états-unis

Homeplace : a site of resistance dans Yearning: race, gender, and cultural politics - Hooks, Bell (Yearning: race, gender, and cultural politics, 1990)
bell hooks crosses boundaries in major debates on postmodern theory, cultural criticism, and the politics of race and gender. She warns that “discourse” about “difference” is dangerously detachable from more essential struggles.
Section: 236 p
Keywords: 1900-1999; 1980-1989; afro-féminisme; amérique du nord; amériques; antiracisme; approches et analyses; cours; discipline; féminisme afroaméricain; histoire et politique; patriarcat; premier cycle; périodes historiques; racisme; régions géographiques; sciences humaines; soc3113; sociologie; systèmes d'oppressions; thématiques; violences; états-unis